Use of Community Science Data to Assess Factors Associated With Diamond‐Backed Terrapin (Malaclemys terrapin) Sightings in Coastal Marshes of Southeastern North Carolina, USA - Morgan Whitmer; Elizabeth Pinnix; Sarah Finn; Jessie Jarvis; Hope Sutton; Amanda Southwood Williard (Ecology and Evolution, 2025)
ABSTRACT The diamond‐backed terrapin (Malaclemys terrapin Schoepff, 1793) is an elusive species that is difficult to study due to its semi‐aquatic nature and a lack of specific information about where populations occur. The aim of this study was to assess the factors associated with diamond‐backed terrapin sightings at two estuarine monitoring sites in North Carolina using data collected via community science head count surveys. Incorporating community scientists into long‐term ecological studies allows researchers to increase the scope of data collection while engaging community members in conservation efforts for species of concern. Diamond‐backed terrapin sighting data were used as the response variable in binomial models that included time of day, air temperature, habitat type, season, and distance from the nearest possible nesting location as explanatory variables. Diamond‐backed terrapins were significantly more likely to be sighted during morning surveys and during Spring compared with Fall at both study sites. There was a negative correlation between air temperature and diamond‐backed terrapin sightings. At one of the two study sites, there was a positive correlation between distance from the nearest possible nesting beach and diamond‐backed terrapin sightings, and diamond‐backed terrapins were significantly more likely to be sighted in aquatic habitats with mud substrate. Spatial and temporal patterns in diamond‐backed terrapin sightings may be influenced by foraging patterns and behaviors associated with thermal and osmotic regulation, as well as environmental conditions that affect detectability. The results of this study lay the groundwork for additional studies of diamond‐backed terrapin presence and abundance at our study sites, expansion of survey efforts into different regions, and broader efforts to assess population responses to environmental and anthropogenic stressors in this salt marsh species.